Formulation and Evaluation of Optimized Oxybenzone Microsponge Gel for Topical Delivery. (18th February 2015) - Pawar, Atmaram P.; Gholap, Aditya P.; Kuchekar, Ashwin B.; Bothiraja, C.; Mali, Ashwin J.
Abstract : Background . Oxybenzone, a broad spectrum sunscreen agent widely used in the form of lotion and cream, has been reported to cause skin irritation, dermatitis, and systemic absorption. Aim . The objective of the present study was to formulate oxybenzone loaded microsponge gel for enhanced sun protection factor with reduced toxicity. Material and Method . Microsponge for topical delivery of oxybenzone was successfully prepared by quasiemulsion solvent diffusion method. The effects of ethyl cellulose and dichloromethane were optimized by the 3 2 factorial design. The optimized microsponges were dispersed into the hydrogel and further evaluated. Results . The microsponges were spherical with pore size in the range of 0.10–0.22  µ m. The optimized formulation possesses the particle size and entrapment efficiency of 72 ± 0.77  µ m and 96.9 ± 0.52%, respectively. The microsponge gel showed the controlled release and was nonirritant to the rat skin. In creep recovery test it had shown highest recovery indicating elasticity. The controlled release of oxybenzone from microsponge and barrier effect of gel result in prolonged retention of oxybenzone with reduced permeation activity. Conclusion . Evaluation study revealed remarkable and enhanced topical retention of oxybenzone for prolonged period of time. It also showed the enhanced sun protection factor compared to the marketed preparation with reduced irritation and toxicity.